EFFICACY OF MANUAL ACUPUNCTURE ON FUNCTIONAL DYSPEPSIA: A META-ANALYSIS OF RANDOMIZED, CONTROLLED TRIALS - Yuan, Xing-xing; Wang, Bing-yu; Yang, Lei; Li, Dan-dan; Liang, Hao; Zhang, Ya-li (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: This study aimed to systematically review the randomized controlled trials on the efficacy of applying manual acupuncture to functional dyspepsia (FD) compared with conventional gastrointestinal (GI) tract regulator medications. Methods and Materials: Electronic data bases including the Cochrane Library, PubMed, Embase, Chinese Scientific Journal database (VIP database), China National Knowledge Infrastructure (CKNI), Wan-fang Database and Sino-Med were searched for randomized controlled trials. Utilized data included those published before 30th, Jul. 2016. Manual search on conference abstracts and reference lists was further conducted. Risk of bias evaluation, meta-analysis, sensitivity analysis and all extracted information were performed. Results: A total of 31 RCTs studies including 2571 participants were identified that include 1314 participants in the groups of manual acupuncture and 1257 participants in the control groups. The result demonstrated that manual acupuncture is more effective in the total effective rate than GI tract regulator medications (OR=3.00, 95%CI [2.33,3.87], p<0.00001,). In addition, manual acupuncture also shows a higher excellent rate than GI tract regulator medications (OR=2.51, 95% CI [2.08,3.03], p<0.00001). The analysis also showed that manual acupuncture improved symptom scores (WMD=-1.21, 95%CI [-2.13,-0.30], p=0.009) and motilin level (WMD=13.99, 95%CI [0.45,27.54], p=0.04) of functional dyspepsia significantly compared to GI tract regulator medications. No serious side-effect was observed in both GI tract regulator medications groups and manual acupuncture groups. Conclusion: The evidence shows that, compared to the GI tract regulator medications, manual acupuncture can significantly improve the total effective rate, excellent rate, symptoms of functional dyspepsia and motilin levels. However, a larger, long-term, rigorous designed trial is necessary.